(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article explores the linguocultural characteristics of profession-related clothing names in Uzbek and English languages. It analyzes how occupational clothing terms reflect cultural values, historical traditions, and social structures. The study shows that clothing terminology is not only a linguistic phenomenon but also a cultural marker that encodes national identity, professional hierarchy, and social norms in both languages.